The investigation of the folding pathway of trp-cage miniprotein using explicit solvent molecular dynamics simulation - Ahmad Khairudin, Nurul Bahiyah (2015)
The objective of this study is to investigate the folding pathway of Trp-cage miniprotein. The structure and trajectories of this protein has been studied using Molecular Dynamics (MD) simulation. The simulation was run at 300K for 250ns. Clustering analysis was conducted to group the trajectories according to the RMSD value and six clusters were generated. From this, the best conformation was identified to best represent the Trp-cage miniprotein. The formation of the hydrogen bond that involved Gly11-Ser14 assisted the formation of 3 10 -helix. In this study, it is strongly suggested that the hydrogen bond interactions determined the formation of secondary structures.